explique x-1/4x²- 3/2x = 1/6x
resolva
Soluções para a tarefa
Respondido por
1
Boa tarde
x - x²/4 - 3x/2 = x/6
x - x²/4 - 3x/2 - x/6 = 0
12x - 3x² - 18x - 2x = 0
-3x² - 8x = 0
3x² + 8x = 0
x*(3x + 8) = 0
x1 = 0
x2 = -8/3
x - x²/4 - 3x/2 = x/6
x - x²/4 - 3x/2 - x/6 = 0
12x - 3x² - 18x - 2x = 0
-3x² - 8x = 0
3x² + 8x = 0
x*(3x + 8) = 0
x1 = 0
x2 = -8/3
Perguntas interessantes
Matemática,
11 meses atrás
Inglês,
11 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás